Relationship Between COVID-19 Vaccination Status and Maternal, Neonatal, and Placental Outcomes - Leo Jumadi Simanjuntak (Jurnal EduHealth, 2023)
It cannot be denied that the Covid-19 pandemic has caused a huge blow to the entire fabric of life in all areas, including the economy, including maternal and perinatal health.Globally, it has been reported that worsening maternal and perinatal outcomes include increased maternal deaths, stillbirths, ruptured ectopic pregnancies and the incidence of maternal depression.Several researchers reported that there was no significant relationship between Covid-19 vaccination and an increased incidence of maternal and neonatal morbidity compared to populations who did not receive the Covid-19 vaccine.